(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Abstract: This article analyzes the processes of glacier retreat in the mountainous regions of Central Asia under conditions of global climate change and their impact on the region’s water resources. During the study, the state of glaciers in the Tien Shan and Pamir-Alay mountain systems, as well as the dynamics of changes in their area and volume, were examined. Based on remote sensing data and geographic information systems (GIS), the spatial characteristics of glacier degradation were identified. The results show that the rapid melting of glaciers initially leads to a temporary increase in river discharge; however, in the long term, it intensifies water resource scarcity. It was also determined that glacier retreat increases the risk of mudflows, landslides, and other natural hazards. The research findings serve as a scientific basis for developing sustainable water resource management and climate change adaptation strategies in Central Asia.